EFEKTIVITAS PELET BIOFUNGISIDA Trichoderma harzianum MENGENDALIKAN Fusarium sp. PENYEBAB PENYAKIT REBAH SEMAI PADA BIBIT TANAMAN CAISIM (Brassica rapa var. parachinensis L) - Rubiati Fadhilah; Juni Safitri Muljowati; Endang Sri Purwati (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
This research aimed to determine the effect of the interaction of the dosage with the application model of Trichoderma harzianum bio-fungicide pellet to the effectiveness of damping-off disease control caused by Fusarium sp. on the green mustard, and also to determine the most effective dosage and application model to control that disease. This research was experimental with the factorial completely randomized design. The factors were: the dosage of T. harzianum bio-fungicide pellet, i.e., 0 g (D0), 12,5 g (D1), 25 g (D2), 37,5 g (D3), 50 g (D4), 62,5 g (D5), and 75 g (D6); and the application model of pellet, i.e., T1, T2, T3 dan T4. This research analyzed the data using the test of variety difference with 5% and 1% degree of errors, followed by least significance difference test. The results showed the interaction between dosage and application model did not affect the effectiveness of the damping-off disease control on the green mustard seedling. The dosage of T. harzianum pellets and the application model of T. harzianum pellets independently gave a significant effect on the effectiveness of biological control agent of T. harzianum toward Fusarium sp. on the green mustard seedling. The dosage of 37,5 g per 50 green mustard individuals was the most efficient amount to control the damping-off disease. The 7-day continuous application and incubation of pellet to the seeding medium before pathogen inoculation and planting were better than any other application models.